2016
DOI: 10.1177/1535370216681553
|View full text |Cite|
|
Sign up to set email alerts
|

Sericin ameliorated dysmorphic mitochondria in high-cholesterol diet/streptozotocin rat by antioxidative property

Abstract: The present work provides new insights regarding the antioxidative effect of sericin in (i) reducing blood cholesterol, (ii) improving liver and heart mitochondrial structures, (iii) maintaining endoplasmic reticulum integrity in exocrine pancreatic glands, and (iv) inhibiting fat deposition in the liver. Electron microscopic, histopathologic, immunohistochemical, and biochemical studies were performed. All of the results demonstrate the efficacy of sericin as a candidate for development of a functional food o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
4

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 40 publications
1
34
0
4
Order By: Relevance
“…In agreement with our previous report indicating anti-oxidative properties of sericin in the heart and liver mitochondria, as shown by oxidative stress markers (e.g. superoxide dismutase, MDA and NRF-2) 1 , 2 , the present proteomics study confirmed that sericin preserves liver mitochondria from oxidative stress by maintaining ACO2 and CPT-II functions.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In agreement with our previous report indicating anti-oxidative properties of sericin in the heart and liver mitochondria, as shown by oxidative stress markers (e.g. superoxide dismutase, MDA and NRF-2) 1 , 2 , the present proteomics study confirmed that sericin preserves liver mitochondria from oxidative stress by maintaining ACO2 and CPT-II functions.…”
Section: Discussionsupporting
confidence: 93%
“…Several mechanisms, mainly focussing on competitive effects on cholesterol absorption, retardation of lipidogenesis in the liver and anti-oxidative properties, have been postulated. Our recent studies 1 , 2 have demonstrated that sericin improves dyslipidaemia and liver or heart mitochondrial architecture via its anti-oxidative activity, as characterised by the reduction in mitochondrial reactive oxygen species, downregulation of malondialdedhyde (MDA) and upregulation of nuclear factor erythroid 2-related factor (NRF-2). In addition, sericin increases lipase activity by enhancing pancreatic and adrenal gland biosynthesis via aquaporin-1 and tubulib-4β proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Mitochondria extraction and electron microscopy. The mitochondria from the hippocampal tissues were extracted 12 h after HSR (n= 6 per group) (17). Briefly, the hippocampal tissue homogenates were centrifuged twice at 1,000 x g and 4˚C for 5 min, and the supernatant was centrifuged at 15,000 x g and 4˚C for 2 min.…”
Section: Mri Studymentioning
confidence: 99%
“…4). These findings likely indicate that increases in AQP- According to mitochondrial function and its architecture, mitochondrial dysfunction is a crucial factor in the pathogenesis of diabetic kidney diseases regarding reactive oxygen species overproduction, apoptosis activation and mitophagy defects [28][29][30][31][32][33][34]. The kidney is an extreme oxygen consumption organ, which renders it sensitive to mitochondrial dysfunction.…”
Section: Discussionmentioning
confidence: 91%
“…Consequent to the acclimatisation period, all rats were fasted for 6 h before being intraperitoneally infected with a single dose of 45 mg/kg streptozotocin (Sigma-Aldrich, USA) in fresh 0.1 M citrate buffer, pH 4.0 to induce hyperglycaemia [34]. Fasting blood glucose was examined in all of the rats, and a blood sugar level of ≥200 mg/dL was considered diabetic stage.…”
Section: Stz-induced Hyperglycaemic Rat Modelmentioning
confidence: 99%